Qual é a forma reduzida da expressão:
![(m + 2n){2} - (m + n) +{2} \: m \: n (m + 2n){2} - (m + n) +{2} \: m \: n](https://tex.z-dn.net/?f=%28m+%2B+2n%29%7B2%7D+-+%28m+%2B+n%29+%2B%7B2%7D+%5C%3A+m+%5C%3A+n)
ME AJUDA PLEASEEE
Soluções para a tarefa
Respondido por
1
(m+2n)²-(m+n)+2mn=
(m+2n).(m+2n) - (m+n) +2mn=
(m²+2mn+2mn+4n²) - (m+n) + 2mn=
m²+4mn+4n² -m -n +2mn=
m²+6mn -m-n +4n².
(m+2n).(m+2n) - (m+n) +2mn=
(m²+2mn+2mn+4n²) - (m+n) + 2mn=
m²+4mn+4n² -m -n +2mn=
m²+6mn -m-n +4n².
Perguntas interessantes